The Interrelationship Between Integrated Posterolateral Hip Stabilizer Strength and Dynamic Lateral Functional Agility in Healthy Young Adult Females: An Expanded Pilot Inquiry - Yu, JaeHo (Journal of Neonatal Surgery, 2025)
This pilot study aimed to elucidate the intricate relationship between the composite strength of posterolateral hip stabilizers and lateral functional agility in healthy young adult females. Employing the Hip Stability Isometric Test (HipSIT) and the Side-Hop Test (SHT), the research explored whether three-dimensionally assessed hip strength could be a meaningful predictor of lateral movement proficiency. A total of 11 participants underwent standardized assessment protocols, and a statistically significant inverse correlation (r = -0.725, p < 0.02) was found. These findings underscore the utility of multidimensional hip strength assessments in predicting athletic performance and suggest practical applications in preventive rehabilitation